The system of subjects of intellectual property law in the conditions of the cyberspace formation - O. Ye. Avramova (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to identifying the system of subjects of intellectual property law in the conditions of the formation of cyberspace. The topic of the article covers the subject composition of intellectual property legal relations. The purpose of the article is to define the system of subjects of intellectual property law, taking into account the virtual and digital aspect.